3rd International Conference on Radiation Safety & Security in Healthcare Services Proceedings of the Thirs, ICRSSHS, Dewan Budaya USM, Penang, Malaysia - Zainon, R. (Lecture Notes in Bioengineering, 2018)
This book presents the proceedings of the 3rd International Conference on Radiation Safety & Security in Healthcare Services. The conference was held at Universiti Sains Malaysia in Penang on 19th-20th August 2017.